Case Report: Fabry disease overlapping with systemic lupus erythematosus in a pediatric patient - Liu, Yaqing; Luo, Juanjuan; Wu, Nengjing; Luo, Kaiyuan; Liu, Jialing; Sun, Liangzhong (Frontiers in Immunology, 2025)
Fabry disease (FD) is an X-linked lysosomal storage disease caused by a deficiency of the enzyme alpha-galactosidase (α-Gal). Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multisystem involvement and predominantly affects women of childbearing age. FD and SLE affect similar organs and may show overlapping features. However, the coexistence of FD with SLE is an infrequent incidence. A 12-year-old Chinese boy was diagnosed to have SLE based on the symptoms of fever, glomerular hematuria, nephrotic-range proteinuria, hypocomplementaemia, and positivity for antinuclear antibodies and anti-double-stranded deoxyribonucleic acid antibodies. Light microscopy of kidney biopsy samples revealed characteristic features of SLE (Classification IV+V). Additionally, electron microscopy of the biopsy samples demonstrated osmiophilic myelin-like bodies in the cytoplasm of glomerular podocytes.The leukocytic α-GLA activity was abnormally low. Genetic analysis showed that the patient was hemizygous for the c.G735C mutation in exon 5 of the GLA gene, which was inherited from his mother and maternal grandmother who were heterozygous and asymptomatic. Hydroxychloroquine (HCQ) administration was discontinued based on renal pathological examination results. The patient was commenced on methylprednisolone pulses and intravenous cyclophosphamide administration, followed by maintenance therapy. He was also treated with angiotensin-converting enzyme inhibitors and an angiotensin receptor blocker. This treatment regimen led to only partial improvement in the patient’s condition. Enzyme replacement therapy (ERT) with agalsidase-α (0.2 mg/kg intravenous administration every 2 weeks) was initiated 2 months after diagnosis. The complement levels remained persistently low. Moreover, treatment with belimumab failed to improve the levels of serological markers. Following the comprehensive treatment regimen, the proteinuria levels remained stable at below 500 mg/24 h. To the best of our knowledge, we report here the case of the youngest patient with a novel FD-related mutation coexistent with SLE. Renal biopsy plays a critical role as an indicator of FD coexisting with nephropathy. Furthermore, genetic testing could serve as a crucial assessment, particularly for male patients with SLE. This case report also addressed the controversial issue of HCQ use in patients with coexistent FD and SLE, examined the effect of ERT on proteinuria, and assessed the role of complement activation in disease progression and treatment.